PENGARUH LINGKUNGAN KERJA DAN MOTIVASI INTRINSIK TERHADAP KOMITMEN AFEKTIF DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Ignatius Soni Kurniawan; Jajuk Herawati; Rika Nuraisyah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to examine the effect of work environment and intrinsic motivation on affective commitment with employee job satisfaction as a mediator. The study used a population of all employees of Kantor Dinas Perdagangan Lampung Tengah. The sampling technique used in this study was accidental sampling on 52 respondents who were determined from the population using the Slovin formula. The data was processed using multiple linear regression analysis and Sobel test. The research findings indicate that the work environment has a direct effect on affective commitment and an indirect effect on job satisfaction. Intrinsic motivation does not affect organizational affective commitment directly, but intrinsic motivation can affect organizational affective commitment if through job satisfaction or through mediation. The implications of the research results are discussed in the discussion section.Keywords: intrinsic motivation; job satisfaction; organizational affective commitment; and work environment.